2022
DOI: 10.1177/15347354221075576
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Yoga Therapy on Heart Rate Variability and Patient-Reported Outcomes After Cancer Treatment: A Study Protocol

Abstract: Background: Following cancer treatment, adults commonly report worsened patient-reported outcomes (PROs) such as anxiety, stress, depression, persistent and upsetting cognitive complaints, unrelenting fatigue, and reduced quality of life. Poorer PROs are associated with disrupted autonomic nervous system functioning as measured by heart rate variability (HRV), both of which have been associated with greater morbidity and mortality. Interventions to improve HRV and PROs among adults following cancer treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…38 On the other hand, physical activities such as exercise and yoga have shown improved HRV indices with reduced long-term mortality. 39,40 Longitudinal studies on the autonomic function of cancer patients have shown that treatment-related factors, such as chemotherapy and radiation therapy, can lead to changes in heart rate variability (HRV) and autonomic nervous system activity. 41 After the completion of treatment, HRV measurements in cancer patients can show persistent autonomic dysfunction, including decreased HRV, decreased vagal activity, and increased sympathetic activity, with reduced overall health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 On the other hand, physical activities such as exercise and yoga have shown improved HRV indices with reduced long-term mortality. 39,40 Longitudinal studies on the autonomic function of cancer patients have shown that treatment-related factors, such as chemotherapy and radiation therapy, can lead to changes in heart rate variability (HRV) and autonomic nervous system activity. 41 After the completion of treatment, HRV measurements in cancer patients can show persistent autonomic dysfunction, including decreased HRV, decreased vagal activity, and increased sympathetic activity, with reduced overall health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“… 38 On the other hand, physical activities such as exercise and yoga have shown improved HRV indices with reduced long-term mortality. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%